Studying the cooling stage in fused filament fabrication - Covas, J. A. (2020)
Fused Filament Fabrication (FFF) is one of the available techniques that is capable of producing parts by additive manufacturing, i.e., by depositing thin filaments of thermoplastic polymers or composites onto a support as a vertical series of horizontal 2D slices of a 3D part. This chapter approaches FFF from a phenomenological point of view, and then focus on the deposition and cooling stage. A code capable of predicting the evolution of temperature during deposition and until cooling is completed, as well as of the final bonding between filaments is presented. The tool is then used to enlighten the effect of major processing parameters on the quality of parts.